Controlling the optical response of 2D matter in standing waves - Plum, Eric (2020)
There is a major development unfolding in photonic technology that promises to impact optical data processing, spectroscopy, and nonlinear/quantum optics. This new direction relates to plasmonics, metamaterials and coherent optics. It exploits the difference in manifestations of optical properties of thin films in traveling waves and standing waves. In standing waves, “coherent control” of the energy exchange between incident and scattered waves leads to new technological opportunities including single photon gates, 100 THz all-optical modulators, sophisticated spectroscopy techniques that can for example distinguish different multipole contributions to absorption and quantum optical devices. We provide an overview of the rapidly growing body of work on the optics of films and metasurfaces in coherent light fields.